Facilitators’ perception of government’s involvement in adult basic literacy programmes in Awka South Local Government Area - Chukwuemerie, O. C.; Okoye, P. U.; Ugwueze, C. M. (Journal of Research in Adult and Continuing Education, 2023)
Adult education has been globally recognized as the education for development but some issues such as inadequate government involvement constrains the effective running of adult literacy programmes thereby limiting its potentials. This study assessed the perception of facilitators on government’s involvement in adult literacy programmes in Awka South Local Government Area. Descriptive survey design was used. The population of the study consisted of all the 34 facilitators in adult basic literacy centres in Awka South Local Government Area. There was no need for sampling because the population was small and manageable. Three research questions were formulated to guide the study. A questionnaire designed by the researchers, based on a four-point scale, was the instrument for data collection from the facilitators. Data collected from responses to their questionnaire were quantified and analyzed using mean statistics. The study found that in the perception of facilitators, government adequately provided funds, teaching aids and other infrastructures and as well periodically organized workshops for facilitators in adult literacy centres in Awka South LGA. The study recommended among other things that successive governments should continue to adequately finance literacy programmes and that host communities and local government areas hosting adult literacy centres should hold government responsible by ensuring that each centre gets its dues and that whatever is provided is properly maintained.